A quranic guide on ethical Halal policy of recombinant collagen-like protein and its challenges in the digital era - Fatah Yasin, Raudlotul Firdaus; Zainan Nazri, Nurul Jannah; Burhanuddin, Norhazirah (2019)
This paper discusses about the issues in producing of collagen-like protein. In this digital era, it is stated that there are existing challenges in the production of Halal recombinant collagen-like protein. Initially, a number of collagen-like proteins have been recognised in bacteria during the last ten years, plenty of challenges are identified. The objective of this paper is to solve the challenges of recombinant collagen-like protein to overcome the high demands of collagen in this digital era, limited supplies of collagen alternative, difficulty in addressing the post-translational modification of recombinant human collagen and the Halal certification of the material itself. It relies on inductive methodology to collect the Qur'anic verses as well as Hadith that related to face the challenges of recombinant collagen-like protein and the analytical method to analyse Qur'anic verses and Sunnah associated with this subject. The findings may also provide a better understanding of issues of Halal policy on recombinant collagen-like protein acceptance on the concept.